Microbiological and physical-chemical analysis of milk produced in Santana do Livramento City – Rio Grande do Sul (Research, Society and Development, 2021)
Milk is a product rich in nutrients and is part of the population's diet. Milk production in Brazil has great importance in the economy, and the prospects for increased production and consumption in the coming years are high. Rio Grande do Sul is a large producer, and much of the milk produced in the state comes from small producers and family farming systems. Due to the large consumption of milk and dairy products, there must be a concern on the part of producers with the quality of the milk produced, since, nowadays consumers are increasingly concerned with the quality of the products consumed, in addition, the issue of quality it is a requirement of legislation and industry. For this to happen, a series of requirements for Good Agricultural and Production Practices must be taken. Thus, the objective of the research was to verify the microbiological and physical-chemical quality of the milk produced in the city of Santana do Livramento-Rio Grande do Sul. With the results obtained, we can observe that in relation to the physical-chemical standards, almost all the producers met the parameters required by the legislation. Regarding the Standard Plate Count, 73.33% of the producers have low count standards with values ​​of 4,200 UFC / mL up to 200,000 UFC / mL, which indicates good hygiene conditions and good practices in their processes. It is concluded that the milk of the analyzed producers meets, in its majority, the physical-chemical and microbiological requirements established by the legislation, which indicates a concern on the part of these producers with quality.